2022
DOI: 10.3389/fnut.2022.898782
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolic Signatures of Healthy Overweight Subjects Challenged With an Oral Glucose Tolerance Test

Abstract: Insulin secretion following ingestion of a carbohydrate load affects a multitude of metabolic pathways that simultaneously change direction and quantity of interorgan fluxes of sugars, lipids and amino acids. In the present study, we aimed at identifying markers associated with differential responses to an OGTT a population of healthy adults. By use of three metabolite profiling platforms, we assessed these postprandial responses of a total of 202 metabolites in plasma of 72 healthy volunteers undergoing compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Shah et al. [ 49 ] reported similar findings with a linear relationship between the level of plasma BCAA at baseline and improved insulin sensitivity induced by weight loss [ 50 ]. Moreover, a novel observation in our study was that plasma concentration of DCA was at least 100% higher throughout the OGTT and MMTT in participants with improved insulin sensitivity after weight loss.…”
Section: Discussionmentioning
confidence: 67%
“…Shah et al. [ 49 ] reported similar findings with a linear relationship between the level of plasma BCAA at baseline and improved insulin sensitivity induced by weight loss [ 50 ]. Moreover, a novel observation in our study was that plasma concentration of DCA was at least 100% higher throughout the OGTT and MMTT in participants with improved insulin sensitivity after weight loss.…”
Section: Discussionmentioning
confidence: 67%
“…39 Negative feedback of cholesterol metabolism leading to reduced bile acid metabolites in the liver upstream of LXRα may contribute to reduced AKR1C4 expression and altered NTX metabolism. Post-prandial changes in fatty acid concentrations may also contribute to altered AKR1C4 activity 11,14 and the food effect detected in this study. Sex-dependent effects on AKR1C4 activity as a function of testosterone and progesterone exposure are not expected due to the supraphysiologic concentrations required for inhibition.…”
Section: Discussionmentioning
confidence: 74%
“…AKR1C4 activity is inhibited by fatty acids at physiologically relevant plasma concentrations 11,12 . Both bile acid metabolites and fatty acid concentrations change in response to food intake 13–15 . Together, this suggests the possibility of acute dietary modulation of AKR1C4; however, the clinical relevance is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics studies have identified BA as the most responsive group of plasma metabolites in healthy human volunteers when challenged with an oral glucose tolerance test (OGTT) ( 6 , 7 ). Although BA are efficiently extracted from the portal blood when passing the liver, a fraction of BA escapes this first-pass hepatic extraction and spills over to systemic circulation.…”
Section: Introductionmentioning
confidence: 99%